2018
DOI: 10.3390/su10082624
|View full text |Cite
|
Sign up to set email alerts
|

Economic Transition and Changing Location of Manufacturing Industry in China: A Study of the Yangtze River Delta

Abstract: Industrial restructuring is widely considered an important force in regional economic growth and sustainable development. With increased globalization and economic transition, a dramatic industrial restructuring has been taking place in China. Applying geographically weighted shift-share model (GW-SSM) and geographically and temporally weighted regression model (GTWR), we analyze (re)location dynamics and determinants of the manufacturing industry in the Yangtze River Delta (YRD) from 1999 to 2013, with partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 69 publications
1
24
0
Order By: Relevance
“…We found that since 1990, most industries in the YRD have formed distinct spatial patterns of specialization and spatial division of labor. For example, the manufacturing has transferred from the north-central region to the north, and most regional core cities have experienced deindustrialization processes, this finding stands in line with recent studies on manufacturing relocation in YRD [61]. High-end industries are clustering to the three biggest core cities of Shanghai (A1), Nanjing (B1), and Hangzhou (C1), while the northern cities of YRD are more specialized in scientific research and polytechnic services.…”
Section: Discussionsupporting
confidence: 82%
“…We found that since 1990, most industries in the YRD have formed distinct spatial patterns of specialization and spatial division of labor. For example, the manufacturing has transferred from the north-central region to the north, and most regional core cities have experienced deindustrialization processes, this finding stands in line with recent studies on manufacturing relocation in YRD [61]. High-end industries are clustering to the three biggest core cities of Shanghai (A1), Nanjing (B1), and Hangzhou (C1), while the northern cities of YRD are more specialized in scientific research and polytechnic services.…”
Section: Discussionsupporting
confidence: 82%
“…GTWR deals with both spatial and temporal nonstationarities simultaneously by constructing a weight matrix based on spatiotemporal distance. GTWR greatly expands the boundary of local modeling techniques, and has been applied in various fields, such as environment, economics, sociology, and so on [24,[26][27][28][29][30]. As a special case of GTWR, GWR ignores the temporal non-stationarity, while TWR (temporally weighted regression) ignores the spatial non-stationarity thus that GTWR integrates GWR and TWR into one uniform framework.…”
Section: Introductionmentioning
confidence: 99%
“…Confronted with the severe environmental pollution caused by industrial production, many countries have been keen on developing strategic, innovative, and profitable industries to proceed with higher quality development and strive to achieve a balance between economic development and environmental protection [64,65]. Thus, industrial structure evolution is widely considered as an important force in sustainable development [12]. Meanwhile, the advent of the global economy, the expansion of technological knowledge, and the growth of the knowledge production have made higher education inclusive and directly responsible for industrial structure evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, despite large amounts of investment, Nolan [11] found that these policies had not resulted in the creation of corresponding competitive technologies to help China improve its industrial structure. On the contrary, the industrialization model of China has remained resource-intensive and brought about increasingly severe environmental pollution and ecological deterioration, which have endangered regional sustainable development [12]. Further, China's lag in industrial evolution is becoming restrictive and confines Chinese enterprises to lower-end industries, thus hindering China's sustained development in a globalised world [13].…”
Section: Introductionmentioning
confidence: 99%